Behavioral risk assessment of work-related musculoskeletal disorders among workers of petrochemical industries: protocol of a mixed method study - Zohreh Moradi; Sedigheh Sadat Tavafian; Fazlollah Ahmadi; Omran Ahmadi (Trials)
Abstract Background Musculoskeletal disorders (MSDs) are one of the most common occupational diseases and the main cause of disability worldwide. Work-related musculoskeletal disorders (WMSDs) are one of the common health risks and the most important cause of absenteeism due to disability in various industries, including the petrochemical industry, in developed and developing countries. These disorders have important social economic, and significant financial consequences due to direct and hidden costs. Health behaviors play a role in both creating and preventing musculoskeletal disorders in employees. Therefore, by identifying the influencing factors on these behaviors, it is possible to strengthen and improve the preventive behaviors of musculoskeletal disorders through educational intervention programs. This study aims to assess the behavioral risk of work-related musculoskeletal disorders, and design and implement an educational intervention to teach effective behaviors in the prevention of musculoskeletal disorders in petrochemical industry workers. Methods This study is a mixed-method study implemented in four stages involving the qualitative study, the design and evaluation of an instrument, the design of an experimental randomized clinical trial, and the psychometric evaluation of the instrument and the evaluation of the program. The research community consists of employees working in the petrochemical industry. The volume of samples in the qualitative study with the purposeful sampling method, in the instrument design stage based on the available sampling method, and also in the experimental study, the samples are employees suffering from work-related musculoskeletal disorders, who were selected based on a simple random method from among the employees of the petrochemical industry. Then they will be divided into intervention and control groups. The instruments of this research include a demographic questionnaire, a researcher-made questionnaire for measuring behavior, and two auxiliary instruments including the visual analog scale (VAS) and the Quebec Disability Scale. Evaluation is done in 4 stages: pre-test, immediately, 3, and 6 months after the intervention of both groups. The obtained data will be analyzed using SPSS software. Discussion Musculoskeletal disorders related (WMSDs) to work can harm employees’ health in various industries, including the petrochemical industry. This study attempts to evaluate the behavioral risk of work-related musculoskeletal disorders among petrochemical industry workers and design and implement an appropriate educational intervention program. Trial registration Iranian Registry of Clinical Trial (IRCT20240321061346N1). Registered on 2024–04-10. Ethics Status: Ethics code: IR.MODARES.REC.1402.251.